Considerations on Drawing as a Representation of Space and an Approach to Knowledge (diségno, 2017)
The values of architectural drawing are multiple: the most immediate is that of drawing as a means for the realization of a work, but perhaps the most important is that of drawing as an instrument for the comprehension of shapes and of the space that is determined by how they follow each other and change. Indeed, anyone who does not draw cannot recognize and remember, or even understand, the shape of objects, of architecture, of the urban environment, of the territory. I agree with Riccardo Migliari, who wrote: “Therefore, whoever does not draw cannot understand space, nor what it means ‘to comprehend space,’ and consequently, whoever does not draw cannot even understand the role of drawing in the formation of this intellectual ability that is so important to the work of an architect” [...].